The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5114/pjr.2021.104856
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: high-resolution computed tomography findings in the first 64 patients admitted to the Hospital of Cremona, the epicentre of the pandemic in Europe

Abstract: In December 2019, a new coronavirus (SARS-CoV-2) was identified as being responsible for the pulmonary infection called COVID-19. On 21 February 2020, the first autochthonous case of COVID-19 was detected in Italy. Our goal is to report the most common chest computed tomography (CT) findings identified in 64 patients, in the initial phase of COVID-19.Methods: Sixty-four chest high-resolution computed tomography (HRCT) examinations performed at the Radiology Unit of the Hospital of Cremona, from 22 to 29 Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Even in our case series, it is confirmed that as the disease progresses the number of lesions can rapidly increase extending to central parenchymal areas and evolving from one type of alteration to another, that is, from GGO alone to GGO with or without crazy-paving up to true areas of parenchymal consolidation, with consequent progression of the TSS. In fact, consistently with the literature data, even in our case series, it has been observed that the highest grades [ 3 , 4 ] are mainly featured by crazy-paving alterations and diffuse areas of parenchymal consolidation.…”
Section: Discussionsupporting
confidence: 92%
“…Even in our case series, it is confirmed that as the disease progresses the number of lesions can rapidly increase extending to central parenchymal areas and evolving from one type of alteration to another, that is, from GGO alone to GGO with or without crazy-paving up to true areas of parenchymal consolidation, with consequent progression of the TSS. In fact, consistently with the literature data, even in our case series, it has been observed that the highest grades [ 3 , 4 ] are mainly featured by crazy-paving alterations and diffuse areas of parenchymal consolidation.…”
Section: Discussionsupporting
confidence: 92%
“…Facilities such as harmonic imaging, compound imaging, color‐ and power‐Doppler imaging (now with new microvasculature techniques), elastography, trapezoid fields of view, and real‐time extended field of view are available on all medium‐to‐high level US scanners and are employed by the operator basing on his/her preferences and on the specific clinical setting 3,4 . At the same time, in the last year, chest US has become quite popular, also owing to the recent Covid‐19 pandemic 5–12 . The normal pleural line is hyperechoic, thin (≤3 mm), and regular.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the COVID-19 outbreak, radiologists were among the first-in-line to diagnose and assess the severity of this disease [ 2 , 3 ]. To properly address the needs of radiology departments, while allowing them to continue to provide standard health care to non-COVID patients, it has been postulated that the organization and workflow of radiology departments during a pandemic needs to change [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%